2015
DOI: 10.7554/elife.09269
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-regulated chromatin switch directs acquisition of flower primordium founder fate

Abstract: Reprogramming of cell identities during development frequently requires changes in the chromatin state that need to be restricted to the correct cell populations. Here we identify an auxin hormone-regulated chromatin state switch that directs reprogramming from transit amplifying to primordium founder cell fate in Arabidopsis inflorescences. Upon auxin sensing, the MONOPTEROS transcription factor recruits SWI/SNF chromatin remodeling ATPases to increase accessibility of the DNA for induction of key regulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(216 citation statements)
references
References 77 publications
9
206
0
1
Order By: Relevance
“…The flexibility of ARF binding to direct or inverted repeats suggests that binding-site orientation may drive differential conformation of the flexible middle region (Fig. 4B), potentially leading to the recruitment of specific coactivators (32,33). Secondary contacts in the PB1 domain could serve to stabilize the conformation of the middle region following DNA binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexibility of ARF binding to direct or inverted repeats suggests that binding-site orientation may drive differential conformation of the flexible middle region (Fig. 4B), potentially leading to the recruitment of specific coactivators (32,33). Secondary contacts in the PB1 domain could serve to stabilize the conformation of the middle region following DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…TPL recruitment and its own multimerization could stabilize ARF-IAA interactions, which would explain why IAAs expressed without TPL fusions are poor repressors in yeast. It is also possible that binding of the IAA to the ARF could lead to conformational changes in the flexible middle region of the ARF that blocks recruitment of coactivators (33,39) or changes the module composition of core transcriptional machinery like the Mediator complex (40). Phosphorylation of the middle region in ARF7 and ARF19 has been shown to inhibit IAA interaction (41), indicating that signal integration from other pathways may take advantage of a link between an IAA interaction and the activity of the ARF middle region.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that, in flower primordia, ARF5 interacts with BRAHMA (BRM) and SPLAYED (SYD) (Wu et al, 2015), both of which are chromatin-remodeling ATPase subunits of the SWI/SNF complex (Wagner and Meyerowitz, 2002;Farrona et al, 2004). Through their interaction with ARF5, BRM and SYD are recruited to promoters of auxin-responsive genes involved in flower formation.…”
Section: Auxin-regulated Chromatin Switchesmentioning
confidence: 99%
“…ARF5 and ARF6 are closely related and known activator ARFs. Recent studies have suggested a role for ARF5 in chromatin unlocking as it interacts with chromatin remodelers of the SWIF/SNF family 25 . Unlocking chromatin makes genes available for transcription and is a plausible mechanism for gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-protein interactions may also regulate the activity of the transcription factor itself as they can interact with other proteins that inhibit their activity 24 . Furthermore, protein-protein interactions may be involved in a third way to increase specific gene regulation: Transcription factors may interact with chromatin remodelers 25 . Changing the state of chromatin can either hide or expose genes, making them available for transcription only at specific moments or specific cell types.…”
Section: Introductionmentioning
confidence: 99%